PENERAPAN PENDIDIKAN KARAKTER MELALUI KEGIATAN KEDISIPLINAN SISWA - Anis Choiriah; Mohammad Zakki Azani (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
Character education is a very important tool in shaping, growing, and developing the personality of students. Education plays a very important role in improving the lives of students to become qualified and useful individuals. The existence of disciplinary activities at school is a benchmark in developing character education. The purpose of this title is to find out the application of character education through student discipline activities at SMP Muhammadiyah 1 Kartasura. Given how important the application of character education is by getting used to living a disciplined life so that students who have a sense of responsibility in carrying out everything and become more effective people. In the application of character education, the role of counseling guidance is also very influential in the process of development and character-building in students. The research method used is a descriptive qualitative method with direct interviews by the teacher concerned through observations and interviews with school parties such as supervising teachers and students of the school. The results of the research obtained related to the application of character education here have been implemented quite well, with the existence of disciplinary activities in the form of ceremonies every Monday, the application of Monday and Thursday fasting at the beginning of each month, dhuha prayers in congregation, tadarus al-Qur'an and muroja'ah together and BTA (reading and writing al-Qur'an) which is carried out in the morning guided by the school with the aim of achieving the school's mission in encouraging graduates who are devoted, qualified, have the skills to live and berakhlaqul karimah.